Analyzing dissemination, quality, and reliability of Chinese brain tumor-related short videos on TikTok and Bilibili: a cross-sectional study - Zhang, Ren; Zhang, Zhiwei; Jie, Hui; Guo, Yi; Liu, Yi; Yang, Yuan; Li, Chuan; Guo, Chenglin (Frontiers in Neurology, 2024)
Background: As the Internet increasingly serves as a crucial source of medical information, the quality and reliability of brain tumor-related short videos on platforms like TikTok and Bilibili remain inadequately evaluated. This study aims to assess these aspects and explore the factors influencing the dissemination of such videos.Methods: A cross-sectional analysis was conducted on the top 100 brain tumor-related short videos from TikTok and Bilibili. The videos were evaluated using the Global Quality Score (GQS) and DISCERN reliability instrument, while an eXtreme Gradient Boosting (XGBoost) algorithm was utilized to predict dissemination outcomes. The videos were categorized by content type and uploader.Results: Videos on TikTok had relatively higher scores on both the Global Quality Score GQS (2, interquartile range IQR [2, 3] in on TikTok; 2, interquartile range IQR [1, 2] on Bilibili, P = 1.51E-04) and the DISCERN reliability instrument (15, interquartile range IQR [13, 18.25] on TikTok; 13.5, interquartile range IQR [11,16] on Bilibili, P = 1.66E-04). Subgroup analysis revealed that videos uploaded by professional individuals and institutions had higher quality and reliability compared to those uploaded by non-professional entities. Videos focusing on disease knowledge exhibited the highest quality and reliability compared to other types. The number of followers was the most important variable in our dissemination prediction model.The overall quality and reliability of brain tumor-related short videos were unsatisfactory on TikTok and Bilibili and did not significantly contribute to video dissemination.Future research should focus on expanding the scope to better understand the dissemination factors of medical-themed videos.